Influence of plant architecture on tritrophic interactions between winter canola (Brassicae napus), Aphids (Hemiptera: Aphididae) and Hippodamia convergens (Coleoptera: Coccinellidae) - Cibils-Stewart, Ximena (Kansas State University, 2013)
Winter canola production in the south-central US is commonly threatened by a complex of aphid species that can cause up to 70% in yield loss. Aphid species vary in their life-history traits, performance (sequestration/excretion of secondary compounds; glucosinolates), vertical distribution within the plant, and temporal dynamics across the growing season. Colonizing behavior of these aphids may be affected by intrinsic characteristics of the host plant (bottom-up effects), such as nutritional value, secondary compounds, or plant architecture. Understanding bottom-up effects may enable the evaluation of plant-level interactions that are influencing predator-prey dynamics. The goal of my research project is to understand aphid population dynamics in different canola plant structures, assess whether aphid quality (sequestration/ excretion of glucosinolates) is influenced by feeding location on the canola plant, and if so, assess the impact on the existing predator communities, specifically the development and fitness of immature and adult Hippodamia convergens. A combination of filed and greenhouse experiments provided novel contributions that will help shape our understanding of key factors regulating aphid population growth in canola fields, which will lead to more judicious use of insecticides and better sampling strategies.
Keywords: Lady beetles; Aphids; Canola; Demography; Aphididae; Coccinellidae; Hippodamia convergens; Brevicoryne brassicae; Myzus persicae; LTRE; Biology (0306); Ecology (0329); Entomology (0353)